2020
DOI: 10.21203/rs.3.rs-25850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of COVID-19 RNA-Dependent RNA Polymerase by Natural Bioactive Compounds: Molecular Docking Analysis

Abstract: Till now there is no approved treatment for COVID-19. Phenolic compounds are known to have antiviral activity against many viruses such as HCV and HIV, through their phenol rings interaction with viral proteins and/or RNA, or via its regulating MAP kinase signaling in host cell defense. The present study aimed to assess polyphenolic compounds (gallic acid, quercetin, caffeine, resveratrol, naringenin, benzoic acid, oleuropein and ellagic acid) as COVID-19 RNA-dependent RNA polymerase (PDB ID 6M71) inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The molecular structure of RdRp was revealed in May 2020 ( Gao Y. et al., 2020 ), providing a new strategy for discovering prophylactic candidates for SARS-CoV-2 inhibition. Abd El-Aziz et al ( El-Aziz Abd et al., 2020 ) investigated the potential of eight natural polyphenols (quercetin, naringenin, caffeine, oleuropein, ellagic acid, benzoic acid, resveratrol, and gallic acid polyphenols) as inhibitors of SARS-CoV-2 RdRp by molecular docking assay. The studied polyphenols formed hydrogen bonds with the nucleotide triphosphate (NTP) entry channel amino acids (ARG 555, ARG 555, LYS 545) in SARS-CoV-2 RdRp (except caffeine and oleuropein).…”
Section: Natural Products Inhibiting Human Coronavirusmentioning
confidence: 99%
“…The molecular structure of RdRp was revealed in May 2020 ( Gao Y. et al., 2020 ), providing a new strategy for discovering prophylactic candidates for SARS-CoV-2 inhibition. Abd El-Aziz et al ( El-Aziz Abd et al., 2020 ) investigated the potential of eight natural polyphenols (quercetin, naringenin, caffeine, oleuropein, ellagic acid, benzoic acid, resveratrol, and gallic acid polyphenols) as inhibitors of SARS-CoV-2 RdRp by molecular docking assay. The studied polyphenols formed hydrogen bonds with the nucleotide triphosphate (NTP) entry channel amino acids (ARG 555, ARG 555, LYS 545) in SARS-CoV-2 RdRp (except caffeine and oleuropein).…”
Section: Natural Products Inhibiting Human Coronavirusmentioning
confidence: 99%
“…In a drug repurposing study performed with the Glide docking module, oleuropein exhibited -9.21 kcal mol -1 (in the absence of Mg 2+ ) and -6.07 kcal mol -1 (in the presence of Mg +2 ) docking scores against the RdRp enzyme (Kandeel et al, 2020). However, in another molecular docking study performed with Chimera 1.8.1, oleuropein showed a binding affinity of -4.59 kcal mol -1 to RdRp and interacted with the amino acids Asp445, Asp452, Tyr455 and Asn552 (Abd El- Aziz et al, 2020). This reported binding free energy value is considerably lower (rather weak) compared with the highly favorable binding affinity (-8.0 kcal mol -1 ) in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Singh et al (2020) showed that theaflavin-3,3′-digallate, theaflavin-3′-gallate, theaflavin-3′- O -gallate, and theaflavin had the highest affinity for RdRp with -9.9, -9.6, -9.6, and -9.3 kcal/mol bonding energy, respectively. EGCG and hesperidin ( Singh et al, 2020 ), isolophirachalcone A ( Parvez et al, 2020 ), gallic acid and resveratrol ( Abd El-Aziz et al, 2020 ) are other polyphenols with anti-SARS-CoV-2 activities through the high binding affinity to RdRp.…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%